Peningkatan Keterampilan Menulis Teks Deskripsi melalui Metode Contextual Teaching and Learning (CTL) Berbantuan Media Vlog pada Siswa Kelas VII SMP Negeri 3 Madiun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low descriptive writing skills of seventh-grade junior high school students, as reflected in their difficulties in generating ideas, selecting appropriate vocabulary, and organizing descriptive texts coherently. The objective of this study was to improve students' descriptive writing skills through the implementation of the Contextual Teaching and Learning (CTL) model assisted by vlog media at SMP Negeri 3 Madiun. This study employed Classroom Action Research (CAR), which was conducted in two cycles. Each cycle consisted of four stages: planning, action, observation, and reflection. The research participants were 31 seventh-grade students of SMP Negeri 3 Madiun in the 2026/2027 academic year. Data were collected through descriptive writing tests, observations, interviews, and documentation. The data were analyzed using descriptive quantitative and qualitative techniques. The success criterion of the study was achieved when at least 85% of the students obtained a score above the Minimum Learning Achievement Criteria (KKTP) of 75. The findings revealed that the implementation of the Contextual Teaching and Learning (CTL) model assisted by vlog media effectively improved students' descriptive writing skills. The mean score increased from 68.90 in the pre-action stage to 77.35 in Cycle I and further improved to 86.58 in Cycle II. Similarly, the percentage of students achieving mastery learning increased from 45.16% in the pre-action stage to 70.97% in Cycle I and reached 90.32% in Cycle II. In addition to improving learning outcomes, the implementation of the CTL model assisted by vlog media also enhanced students' activeness, creativity, and participation throughout the learning process. Therefore, the Contextual Teaching and Learning (CTL) model assisted by vlog media is effective in improving the descriptive writing skills of seventh-grade students at SMP Negeri 3 Madiun. Keywords: Contextual Teaching and Learning (CTL), vlog media, descriptive writing skills, descriptive text, Classroom Action Research